2007
DOI: 10.1177/1082013207077914
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Fiber Obtained from Pumpkin (cucumis moschata duch.) Mesocarp Through Enzymatic Treatment

Abstract: Cell wall-enriched pumpkin ( Cucumis moschata Duch.) powder was submitted to enzymatic hydrolysis by cellulase or hemicellulase in order to evaluate the performance of these cell wall-degrading enzymes on that substrate. Different enzyme-substrate ratios were evaluated and the effect exerted by the buffer on cell wall polysaccharides. Cellulase produced the release of pectin macromolecules which include homogalacturonans side chains, the rhamnogalacturonan I core and rhamnogalacturonan II, in conjunction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 45 publications
1
37
2
Order By: Relevance
“…Cell wallpolysaccharides suffered cleavage when powder was submitted to enzymatic treatment into 0.05 mol dm À3 -citrate buffer (pH 5.2), with the aim of getting soluble fractions essentially constituted by pectins, which can present interesting functional properties for food applications. An enzyme preparation containing cellulase (A) or hemicellulase (B), both commercially used for dough and bread improving, were applied, looking for isolation of pectin fractions with thickener performance like that observed in a previous work using enzymes for laboratory research (Fissore et al, 2007) but with a lower-cost procedure. The yields obtained with the industrial enzymes used in the present work were 4.70 g/100 g (using cellulase; A-fraction) and 6.12 g/100 g (using hemicellulase; B-fraction).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell wallpolysaccharides suffered cleavage when powder was submitted to enzymatic treatment into 0.05 mol dm À3 -citrate buffer (pH 5.2), with the aim of getting soluble fractions essentially constituted by pectins, which can present interesting functional properties for food applications. An enzyme preparation containing cellulase (A) or hemicellulase (B), both commercially used for dough and bread improving, were applied, looking for isolation of pectin fractions with thickener performance like that observed in a previous work using enzymes for laboratory research (Fissore et al, 2007) but with a lower-cost procedure. The yields obtained with the industrial enzymes used in the present work were 4.70 g/100 g (using cellulase; A-fraction) and 6.12 g/100 g (using hemicellulase; B-fraction).…”
Section: Resultsmentioning
confidence: 99%
“…This fraction showed a starch content of 0.16 g/100 g. When purified hemicellulase (SIGMA, USA) has been previously used for the process, by the authors (Fissore et al, 2007), the starch content of fraction isolated was $17 g/100 g (unpublished results), probably due to different activities of both hemicellulases.…”
Section: Hemicellulase Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Cell wall-rich pumpkin (Cucumis moschata Duch.) digestion with cellulase released pectin macromolecules which included linear HG side chains, the RG-I core and RG-II, in conjunction with XGA (Fissore, Ponce, Stortz, Rojas, & Gerschenson, 2007). Lately, polyGalA-branched HG (GaGA) complexes have been shown to be an integral part of Na 2 CO 3 -extracted tomato pectins (Round et al, 2010).…”
Section: A New Hypothetical Modelmentioning
confidence: 99%
“…It has been demonstrated that water-extracted pumpkin polysaccharides possess superior hypoglycaemic properties compared to glibenclamide in alloxan-induced diabetic rats (Zhang, 2004). Additionally, pumpkin is rich in pectin, a type of dietary fibre (Fissore, Ponce, Stortz, Rojas, & Gerschenson, 2007), which when consumed is purported to control glycaemic levels and reduce the need for insulin when fibre-rich foods are consumed by patients with diabetes (Guillon & Champ, 2000).…”
Section: Pumpkins As Anti-diabetic Functional Medicinesmentioning
confidence: 99%